Proteínas de resposta imune expressas na hemolinfa da Diatraea saccharalis (Lepidoptera: crambidae) em resposta a diferentes microrganismos - Corsato, Ana Cláudia Malagutti (2018)
The Diatraea saccharalis is the pest responsible for a great economic loss to the cultivation of sugar cane. As well as others members of Lepidoptera order, the D. saccharalis has a fast and efficient immune innate response, characterized by primary defense barrier, cellular immune response and humoral immune response. The antimicrobial peptides (AMPs) are included in humoral immune response that show cationic and amphiphilic characteristics besides its low molecular weight, what makes them potentially therapeutic agents. In this study were analyzed proteins with low molecular weight differently expressed in the hemolymph of D. saccharalis, after the interval of six and twelve hours of humoral immune response induction with different microorganisms compared to non-challenged worms (control). The 5th instar worms were divided in groups (n= 50) and submitted to six and twelve hours of septic challenges: control (group 1), challenged by Bacillus subtilis ATCC 6623 (group 2), challenged by Escherichia coli ATCC 11229 (group 3), and challenged by Beauveria bassiana 88 strain (group 4). In each worm was inoculated a known concentration of microorganism, and after the established time, the hemolymph was collected. The low molecular weight proteins were obtained submitting each hemolymph sample to an extraction solution containing Methanol, Acetic Acid and Water. After that, the protein extracts were concentrated in columns and protein dosage was realized in 280 nm. About 500 μg of proteins were submitted to two-dimensional electrophoresis (2-DE). The spots were excised from gels, digested with Tripsin and submitted to MALDI-ToF/ToF type mass spectrometry. The identification of protein orthologs was realized using the obtained data against the data available on the MASCOT online server (Matrix science), with the database (NCBI and Swiss rot) specified for Drosophila melanogaster and an internal database of Lepidoptera. The TagIdent tool was utilized for searching proteins through their molecular weight and isoelectric point. It was possible to identify eighteen proteins, of which twelve demonstrated to be involved with immune response in D. saccharalis. The six hours septic challenge with B. subtilis was responsible for modification of expression of Peptidoglycan recognition protein (PGRP), for increase of expression of Chitin-binding protein and for induction of expression of proteins like the Attacin-A and the Serine-protease inhibitor-like. The six hours septic challenge with E. coli increased the expression of a putative defense protein. The twelve hours septic challenge using B. subtilis and E. coli were responsible for increase of expression of Lysozyme. The six hours septic challenge with B. bassiana induced of expression of a Cecropin A2 and a Drosomycin-like. On the order hand, after twelve hours of fungal challenge, there was the induction of expression of multifunctional protein Apolipophorin-3. It was concluded that the septic challenge with different microorganisms were capable of change the expression of some proteins involved in the immune response in D. saccharalis, significant for understanding this process as well as for pointing the substances with antimicrobial functions.